Motor imagery facilitates force field learning - Anwar, Muhammad Nabeel; Tomi, Naoki; Ito, Koji (Brain Research, 2011)
Humans have the ability to produce an internal reproduction of a specific motor action without any overt motor output. Recent findings show that the processes underlying motor imagery are similar to those active during motor execution and both share common neural substrates. This suggests that the imagery of motor movements might play an important role in acquiring new motor skills. In this study we used haptic robot in conjunction with motor imagery technique to improve learning in a robot-based adaptation task. Two groups of subjects performed reaching movements with or without motor imagery in a velocity-dependent and position-dependent mixed force field. The groups performed movements with motor imagery produced higher after effects and decreased muscle co-contraction with respect to no-motor imagery group. These results showed a positive influence of motor imagery on acquiring new motor skill and suggest that motor learning can be facilitated by mental practice and could be used to increase the rate of adaptation. ► The effect of motor imagery on the kinematic performance was examined. ► Two groups performed movements with and without motor imagery. ► We found a positive effect of motor imagery on performance.